REPORTS: THE ACTIVIST PROGRAM AT MOUNTROSE SCHOOL - Cochrane, E. George (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1969)
The very first issue of the McGill Journal of Education (Spring 1966) was concerned with "Activism." This was a popular topic, for the schocls of Quebec were then beginning to try to adopt activist approaches to teaching as they sought to implement the recommendations of the Royal Commission of Inquiry into Education in the Province of Quebec (the Parent Report). The following paper Is a principal's description of the emergence of an activist school. - Ed.